2019
DOI: 10.1109/jstqe.2019.2950802
|View full text |Cite
|
Sign up to set email alerts
|

Material Gain Engineering in Staggered Polar AlGaN/AlN Quantum Wells Dedicated for Deep UV Lasers

Abstract: Material gain is calculated for polar staggered Al x Ga 1-x N/AlN quantum wells (QWs) of various architectures: i) with a step-like Al y Ga 1-y N barrier grown prior the Al x Ga 1-x N QW, ii) with a step-like barrier grown on the QW, and iii) with a step-like barrier grown prior and on the QW. The obtained results are compared with those obtained for reference Al x Ga 1-x N/AlN QWs. With the increase in Al concentration in the reference QW the gain peak blueshifts and its strength decreases mainly due to the A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…In the context of studies reported in this work, the engineering of QW width in broad range can be also very interesting for staggered polar GaInN/GaN and AlGaN/AlN QWs. So far, large widths were not considered for staggered QWs as a drastic decrease in gain with increasing QW width was observed [59]. Since this polar QW system is non-intuitive, considering large widths in staggered QWs can lead to unexpected results, as shown in this paper for rectangular QWs.…”
Section: Aln Capmentioning
confidence: 92%
See 2 more Smart Citations
“…In the context of studies reported in this work, the engineering of QW width in broad range can be also very interesting for staggered polar GaInN/GaN and AlGaN/AlN QWs. So far, large widths were not considered for staggered QWs as a drastic decrease in gain with increasing QW width was observed [59]. Since this polar QW system is non-intuitive, considering large widths in staggered QWs can lead to unexpected results, as shown in this paper for rectangular QWs.…”
Section: Aln Capmentioning
confidence: 92%
“…Figure 5 shows spectra of the TM mode of the material gain calculated for Al0.8Ga0.2N/AlN QWs of different widths at the carrier concentrations of 2.5 and 3.0×10 19 cm -3 . In contrast to the Ga0.8In0.2N/GaN QW, the fundamental transition in this QW is with TM polarization [59] and therefore the TM mode of the material gain is plotted in this figure. The change in the spectral position and the intensity of gain peak is very similar to that observed for Ga0.8In0.2N/GaN QW.…”
Section: Aln Capmentioning
confidence: 99%
See 1 more Smart Citation
“…Quite often, staggered QWs have been considered. [18][19][20][21][22][23][24] In this case, it is possible to obtain a better ground-state electron-hole overlap with appropriate polarization engineering, but the total thickness of the step-like barriers and QW is still below 5 nm, [18][19][20][21] which is very far from the width typical of non-polar QWs in III-V semiconductors, that is, 8-15 nm. [25][26][27][28] In contrast, lasing for wide InGaN QWs has been demonstrated experimentally.…”
Section: Doi: 101002/apxr202200107mentioning
confidence: 99%
“…Interestingly, the staggered MQW structure design has recently been demonstrated in InGaN-based blue LEDs [ 45 ], green LEDs [ 46 ], and AlGaN-based deep UV lasers [ 47 ]. Additionally, the optoelectronic characteristics of InGaN-based green micro-resonant cavity light-emitting diodes (µ-RCLEDs), which consist of a three-layer staggered InGaN MQWs, bottom nanoporous n-GaN DBRs, and top Ta 2 O 5 /SiO 2 DBRs, have been numerically investigated [ 48 ].…”
Section: Introductionmentioning
confidence: 99%